Forms of Conflict in Hazaa Al-Barari’s Plays - Khader Al-Jubouri, Ghanam Mohammed; Abood, Khulood Yousif (Journal of Tikrit University for Humanities, 2020)
War literature has conveyed many events through different literary genres, showing many literary philosophies and depicting the reality of war’s bitter woes. The writer is an eyewitness as he witness war as a recruiter or a journalist and he becomes, in this sense, a true narrator of the bloody events that he experienced, especially if he witnesses the bloody massacres that make him lose many friends who share him the woes of war. In some other cases there are soldiers or officers who participate in war and they narrate him the battles with their daily details and portrayed what disasters they faced. All these irrigated forms and realistic tales make any talented person a literary writer dating to an important stage in the history of mankind at the local level and global levels.